Data-Driven Innovation in the Creative Industries - Melissa Terras; Vikki Jones; Nicola Osborne; Chris Speed (Routledge, 2024)
The creative industries – the place where art, business, and technology meet in economic activity – have been hugely affected by the relatively recent digitalisation (and often monetisation) of work, home, relationships, and leisure. Such trends were accelerated by the global COVID-19 pandemic. This edited collection examines how the creative industries can be supported to make best use of opportunities in digital technology and data-driven innovation. Since digital markets and platforms are now essential for revenue generation and audience engagement, there is a vital need for improved data and digital skills in the creative and cultural sectors. Taking a necessarily global perspective, this book explores the challenges and opportunities of data-driven approaches to creativity in different contexts across the arts, cultural, and heritage sectors. Chapters reach beyond the platforms and approaches provided by the technology sector to delve into the collaborative work that supports innovation around the interdisciplinary and cross-sectoral issues that emerge where data infrastructures and approaches meet creativity. A novel intervention that uniquely centres the role of data in the theory and practice of creative industries' innovation, this book is valuable reading for those researching and studying the creative economy as well for those who drive investment for the creative industries in a digitalised society. The Open Access version of this book, available at www.taylorfrancis.com, has been made available under a Creative Commons Attribution-Non Commercial-No Derivatives (CC-BY-NC-ND) 4.0 International license.
Keywords: 330; creative industries; art; business; technology; economy; creative economy; digitalisation; digitalised society